Renal Biopsy Findings in Lupus Nephritis and Their Correlation with Clinico-Biochemical Parameters (Academia Journal of Medicine, 2019)
Background: This is an observational analysis wherein we contemplated renal biopsy discoveries of 50 patients of lupus nephritis (LN) and these biopsy discoveries were associated with clinical and biochemical parameters of the LN patients. The study included 50 patients of SLE  diagnosed to have renal involvement. Renal biopsy was done in every one of the 50 patients and the outcomes were ordered by the ISN/RPS  arrangement of LN. Clinical and biochemical parameters were examined in all patients and they were corresponded with renal biopsy  discoveries. The different biochemical parameters in our investigation were-proteinuria (100%) , raised serum creatinine (56%). Mean 24 hour  protein discharge was 2386+/ - 1810 mg/day at presentation.11(22%) patients had nephrotic range proteinuria and 8 (16%) patients had  proteinuria
Keywords: Renal biopsy; lupus nephritis; SLE; Clinical & biochemical parameters